PERSAINGAN USAHA DALAM HUKUM ISLAM - Meirina Dewi Pratiwi; Erniwati (Fakultas Hukum Universitas IBA Palembang, 2019)
There are bussiness competition doing by the bussiness performer in bussiness activity. From the benefit side, the competition in bussiness activity is an effective way to reach the optimalization of resources usability. Indonesian bussiness development has brought a lot of conglomerate groups which would also bring the negative effect, such as the low protection to the consument and the small industry. These kind of monopoly thing have become the crucial topic in this country nowadays. If we observe from the Islamic perpective, the small benefits that we got from our bussiness is a lot better than doing the bussiness monopoly things since it is reflected the fairness itself. How is the concept of good Bussiness competition according to the islamic law ? How is the bussiness' code of ethics according to the islamic perspective to create the proper bussiness competition as the purpose of Undang-Undang Tahun 1999 no. 5 ? Market needs to be based on the